Reviews of experiences of big data leading universities in implementing big data / Yang Zheng Li, Ahmad Faiz Yaakob and Farah Adilla Abd Rahman - Yang, Zheng Li; Yaakob, Ahmad Faiz; Abd Rahman, Farah Adilla (2021)
With the gradual introduction of educational information policies and the continuous progress of big data information technology, big data education has entered the application and exploration stage of the collection, storage, analysis, and presentation of big data. In the exploration and application of new technologies, due to the high cost of trial and error, unknown risks and other influencing factors need to be carefully considered and gradually explored. Therefore, it is necessary to find out the key problems, find corresponding solutions, and gradually solve them. The research on fully realizing the process of efficient management of big data in universities will also provide some experience for other countries. Therefore, what is the significance of higher education institutions to implement big data? How do higher education institutions formulate big data policies? The paper is qualitative. The method used in the research is descriptive and analytical. For the descriptive one, I will describe the reasons why and how this university adopts and implement big data. On the other hand, the analytical approach will guide the researcher to explain, review and analyse the progress, problems faced by respective universities and propose some possible recommendations in the implementation of big data in those universities. The method of collecting data is primarily based on available data, articles and government documents, magazines, and the internet.